PENGGUNAAN DESAIN PRODUK RAMAH LINGKUNGAN DAN INOVASI HIJAU PADA UKM DI KOTA BATAM MELALUI PENDEKATAN SYSTEM DYNAMICS - Setiawati; Sundiman, Didi (Fortunate Business Review, 2024)
This study aims to describe a dynamics system model in the use of environmentally friendly product designs and green innovation in SMEs in Batam. This type of research is qualitative research. Sources of data collection in this study were 10 informants of SME players in Batam city. The data is in the form of answer words containing environmentally friendly product design packaging and green innovation. This research data analysis using Vensim software. The result of this research is that through a dynamics systems approach, it can provide policy simulations that are used to consider the application of green innovations that can support an increase in the profit of a business. Through a dynamics system approach, it can provide simulations that the implementation of green innovation strategies can support business sustainability or is called sustainability business.